PENERAPAN AKUNTANSI PERPAJAKAN ATAS KEPEMILIKAN AKTIVA KENDARAAN DENGAN METODE SEWA PEMBIAYAAN PADA CV. KARYA WENANG - Claudia, Stephany Florence; Nangoi, Grace Mogi; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
To fund the business activities especially for the procurement of capital goods, the company has alternative sources of financing in the corporate and finance sourced from outside the company. Funding is sourced from within the company including the capital stock, issuance of bonds, and retained earnings. While the funding is sourced from outside the company such as bank loans and leasing. For companies that not have enough capital, the alternative is often used outside financing companies that finance leases/capital lease. The purpose of this study is to investigate the application of accounting taxation on the ownership of assets by the method of vehicle financing lease ( capital lease ) on the CV. Karya Wenang. The method used in this research is descriptive method. The results of the study on the CV. Karya Wenang is the CV Karya Wenang not fully implement the accounting taxation of finance lease transactions that do. As in the case of depreciation, the company still apply to commercial accounting